Static jump test performance is related to back squat strength in athletes - Haun, C. T.; Martin, J. S.; Gleason, B. H.; Kavanaugh, A. A.; DeWeese, B. H.; Stone, M. H.; Satoshi, M. (International Journal of Sports Science & Coaching, 2017)
We examined a static jump test's relationship with back squat strength in collegiate athletes. Forty-one (n=41) young (aged 20.8 ± 2.4 years), healthy volunteers reported estimated back squat one-repetition maximums and completed a static jump protocol. The static jump protocol included five loading conditions, and jump height was estimated via flight time from portable contact mats. Loading conditions for males (n=19) included 0 kg (polyvinylchloride pipe), 20.42 kg, 43.10 kg, 61.25 kg, and 83.94 kg whereas females (n=22) used 0 kg, 12.70 kg, 20.42 kg, 29.49 kg, and 43.10 kg. Relationships between back squat one-repetition maximums, jump height, ratio (jump height/system mass) at each loading condition, mean jump height and ratio across loading conditions, change in jump height and ratio per condition (dJH, dRatio), and performance slope (slope of best fit line for system mass vs. jump height) were evaluated. Amongst all subjects, large (r>0.70), statistically significant correlations were found between back squat one-repetition maximums and jump height for the two lightest loading conditions, mean jump height, and performance slope. However, relation- ships varied by sex with mean jump height demonstrating the greatest consistency in both males and females. Mean jump height may be the most practical variable from this static jump protocol for monitoring training adaptations, particularly in relatively homogenous female collegiate athlete populations. ABSTRACT FROM AUTHOR